Incorporating Geographic Information Systems (GIS) and archaeological data to better understand spatial and temporal distributions of past societies in Mpumalanga, South Africa - Angel, Jessica (My University, 2014)
The Mpumalanga escarpment hosts a series of stonewalled settlements that occur along a narrow belt between Carolina and Ohrigstad. These sites are unique as they have networks of linking roads, vast areas of terracing as well as large cattle kraals which do not occur in combination or to such an extent anywhere else in southern Africa. Furthermore these settlements occur at an altitude unfavourable for living or agricultural purposes. With the use of Geographic Information Systems (GIS) layers of data relating to the Mpumalanga escarpment and the settlements within the area over the past five hundred years are viewed and compared in order to further understand the placement and structure of these settlements.
Keywords: Geographic information systems.; Archaeology - Geographic information systems.; Archaeology - Methodology.; Land settlement patterns.; Archaeology - South Africa - Mpumalanga.